Clothes Don’t Maketh the Man Nor a Criminal Profiler an Expert Witness - Kocsis, Richard N. (International journal of offender therapy and comparative criminology, 2020)
The article by Kocsis and Palermo, published in 2016, examined the findings of research which had assessed the validity of the investigative technique colloquially known as criminal profiling. These findings were subsequently considered within the framework of their relevance to the admissibility of the technique as a form of expert witness evidence. The overall conclusion was that a discrete facet of the profiling technique may satisfy some of the requisite legal criteria for admissibility in jurisdictions within the United States. However, this conclusion was based upon studies which used samples of senior forensic psychiatrists and psychologists as the tested profilers. In this regard, it was noted that this parameter may preclude the generalization of this conclusion to other professional groups who do not possess such qualifications. Accordingly, the present article explores the potential admissibility of law enforcement personnel who are not qualified forensic mental health practitioners tendering expert witness evidence in the nature of criminal profiling. The conclusion of this analysis is that law enforcement personnel who possess suitable expertise in the analytic task of criminal profiling arguably possess an analogous knowledge base akin to the aforementioned senior forensic psychiatrists and psychologists. On this basis, the conclusions in Kocsis and Palermo, published in 2016, may extend to such personnel and their potential to likewise provide expert witness evidence.